2016
DOI: 10.1007/s10578-016-0650-7
|View full text |Cite
|
Sign up to set email alerts
|

Further Psychometric Evaluation of the Child Disgust Scale

Abstract: This study evaluated the psychometric properties of the Child Disgust Scale (CDS) among 457 youth (ages 8–17, M=14.77±1.98 years) initiating residential treatment for obsessive-compulsive disorder (OCD) and anxiety disorders. Confirmatory factor analysis supported a bifactor model with two distinct factors of Disgust Avoidance and Disgust Affect, in addition to an overall General Disgust factor. Strong internal consistency was observed for the CDS total and factor scores. In addition, CDS scores demonstrated g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In all the cases, a feeling of disgust was the least expressed while watching the tenth session. Nadeau et al, 2016) psychometric evaluation showed that the degree of experienced disgust may vary in the presence of aversive stimuli and is associated with experiencing anxiety. Therefore, it can be stated that Figure 5 pictures decrease of the parental stress when they observed the first and the tenth session.…”
Section: Research Resultsmentioning
confidence: 99%
“…In all the cases, a feeling of disgust was the least expressed while watching the tenth session. Nadeau et al, 2016) psychometric evaluation showed that the degree of experienced disgust may vary in the presence of aversive stimuli and is associated with experiencing anxiety. Therefore, it can be stated that Figure 5 pictures decrease of the parental stress when they observed the first and the tenth session.…”
Section: Research Resultsmentioning
confidence: 99%
“…In Study 1, a group of adults was surveyed about the items they and their children find disgusting. As we noted above, prior measures of disgust sensitivity for children were adapted from adult measures (Muris et al, 2012; Nadeau et al, 2017; Schienle & Schwab, 2019; Viar-Paxton et al, 2015), and theories of a mature theory of disgust focus on abstract concepts, rather than sensory properties (Rozin & Fallon, 1987; for a review, see Rottman et al, 2019). As such, these measures tend to omit questions about uncontaminated foods when examining disgust sensitivity.…”
Section: Study 1: Online Parent Surveymentioning
confidence: 99%
“…The developmental antecedents of disgust (observed in children) are often considered to be immature steps preceding the adult state. For example, rather than eliciting responses from children regarding what they find to be disgusting, disgust sensitivity scales for children have typically been directly adapted from existing adult scales (Muris et al, 2012; Nadeau et al, 2017; Schienle & Schwab, 2019; Viar-Paxton et al, 2015), but without items that might be inappropriate for young children (e.g., those dealing with sexual behavior). In addition, theories of the development of disgust have often focused on the transition from concrete to abstract thinking (for a review, see Rottman et al, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation